2021
DOI: 10.1186/s13756-021-00888-w
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia bacteremia in children: risk factors and mortality rate

Abstract: Purpose Stenotrophomonas maltophilia (S. maltophilia) is an opportunistic and nosocomial pathogen that can cause an invasive and fatal infection, particularly in hospitalized and immunocompromised patients. However, little is known about the impact of S. maltophilia bacteremia in pediatric patients. Therefore, we aimed to identify risk factors for mortality, antibiotics susceptibility to S. maltophilia, and mortality rates in pediatric patients with S. maltophilia bacteremia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
2
33
1
2
Order By: Relevance
“…However, treatment of S. maltophilia infection is difficult due to antimicrobial resistance to a variety of agents; trimethoprim-sulfamethoxazol can continue to be the first choice for the treatment of S. maltophilia. In the study performed by Alsuhaibani et al, [ 33 ] the most effective antibiotic against S. maltophilia isolates was Trimethoprim−sulfamethoxazole (94.1%), which is consistent with our data (100%). Also in the study by Sun et al [ 32 ], the resistance rate of S. maltophilia strains to cefpime, cefotaxime, ceftazidime and gentamicin was 45.1%, 94.1%, 60.8% and 82.4%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…However, treatment of S. maltophilia infection is difficult due to antimicrobial resistance to a variety of agents; trimethoprim-sulfamethoxazol can continue to be the first choice for the treatment of S. maltophilia. In the study performed by Alsuhaibani et al, [ 33 ] the most effective antibiotic against S. maltophilia isolates was Trimethoprim−sulfamethoxazole (94.1%), which is consistent with our data (100%). Also in the study by Sun et al [ 32 ], the resistance rate of S. maltophilia strains to cefpime, cefotaxime, ceftazidime and gentamicin was 45.1%, 94.1%, 60.8% and 82.4%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The susceptibility to TMP/SMX was 92.2%, consistent with the reported studies. 20,21 Although increasing resistance of S. maltophilia to TMP-SMX had been reported, 2 the present study suggested that TMP-SMX might still be suitable as first-line drug for S. maltophilia infection. The susceptibility to minocycline was 94.7%, consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 60%
“…strain I6 showed high similarity (identity ≥ 99.88%) with Stenotrophomonas maltophilia. This species is increasingly reported as an opportunistic and nosocomial pathogens (Alsuhaibani et al 2021 ) and it shows resistance to different antibiotics such as carbapenems and fluoroquinolone (Harmon et al 2019 ; Azimi et al 2021 ; Bostanghadiri et al 2021 ). Results of BLAST and RDP analyses were confirmed by the Bayesian and ML phylogenetic analyses inferred on the basis of the obtained 16S rRNA gene sequences (Fig.…”
Section: Resultsmentioning
confidence: 99%